2015
DOI: 10.1016/j.devcel.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

E2a Is Necessary for Smad2/3-Dependent Transcription and the Direct Repression of lefty during Gastrulation

Abstract: Summary Transcription factor complexes have varied effects on cell fate and behavior, but how this diversification of function occurs is largely unknown. The Nodal signaling pathway has many biological functions that all converge on the transcription factors Smad2/3. Smad2/3 has many cofactors, and alternative usage of these may provide a mechanism for modulating Smad2/3 function. Here we investigated how perturbation of the cofactor E2a affects global patterns of Smad2/3 binding and gene expression during gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Consistent with our hypothesis, siRNA-mediated knockdown of two transcription factors, Tcf3 and Foxa2, is sufficient to up-regulate Mesp1 expression and promote Kdr + mesoderm formation. Mechanistically, Tcf3 is a wellcharacterized target of Id proteins (for review, see Yang et al 2014) and is also known to interact with the Smad/ Foxh1 complex to regulate Smad2/3-dependent transcription in mesendoderm progenitors (Yoon et al 2011;Wills and Baker 2015). In turn, the potent endoderm determinant Foxa2 (Stainier 2002;Viotti et al 2014), is expressed in mesendoderm progenitors in a Smad2-dependent manner in mouse embryos (Vincent et al 2003), suggesting that Tcf3 might cooperate with Smad2 to regulate Foxa2.…”
Section: Molecular Control Of Cardiogenic Mesoderm Specificationmentioning
confidence: 99%
“…Consistent with our hypothesis, siRNA-mediated knockdown of two transcription factors, Tcf3 and Foxa2, is sufficient to up-regulate Mesp1 expression and promote Kdr + mesoderm formation. Mechanistically, Tcf3 is a wellcharacterized target of Id proteins (for review, see Yang et al 2014) and is also known to interact with the Smad/ Foxh1 complex to regulate Smad2/3-dependent transcription in mesendoderm progenitors (Yoon et al 2011;Wills and Baker 2015). In turn, the potent endoderm determinant Foxa2 (Stainier 2002;Viotti et al 2014), is expressed in mesendoderm progenitors in a Smad2-dependent manner in mouse embryos (Vincent et al 2003), suggesting that Tcf3 might cooperate with Smad2 to regulate Foxa2.…”
Section: Molecular Control Of Cardiogenic Mesoderm Specificationmentioning
confidence: 99%
“…We also reported that components of the Nodal signalling pathway were downregulated upon overexpression of E2A homodimers, and conversely upregulated during differentiation of E-protein knockout cells. Interestingly, E2A has also been shown to repress transcription of lefty in Xenopus, with knockout of E2A causing upregulation of lefty and a subsequent failure in mesendodermal fate specification (Wills and Baker, 2015). We propose that E2A could be playing a similar role to repress Nodal signalling in ES cells, but during neural fate commitment -a process in which inhibition of Nodal signalling is already known to be important (Vallier et al, 2004;Watanabe et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
“…In Xenopus embryos, loss of E2A has been associated with inhibition of gastrulation (Yoon et al, 2011). Additionally, E2A and HEB have been shown to be cofactors of the Nodal signalling pathway, both in human ES cells and in Xenopus (Yoon et al, 2011), with E2A playing a dual role to directly repress the Nodal target gene, lefty, during 3 mesendoderm specification in Xenopus, whilst also driving the expression of dorsal cell fate genes (Wills and Baker, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in Xenopus, Nodal signalling is necessary for normal EphA4 expression (Wills and Baker, 2015) in the mesoderm and both signalling pathways are required for the internalization of the mesendoderm (Evren et al, 2014). The presence of this association in both taxa could reflect either convergence or an ancestral state.…”
Section: Relationships Between Fate Specification and Morphogenesis Imentioning
confidence: 99%